Biosurfactant and Degradative Enzymes Mediated Crude Oil Degradation by Bacterium Bacillus subtilis A1 - Parthipan, Punniyakotti; Preetham, Elumalai; Machuca, Laura L.; Rahman, Pattanathu K. S. M.; Murugan, Kadarkarai; Rajasekar, Aruliah (Frontiers in Microbiology, 2017)
In this work, the biodegradation of the crude oil by the potential biosurfactant producing Bacillus subtilis A1 was investigated. The isolate had the ability to synthesize degradative enzymes such as alkane hydroxylase and alcohol dehydrogenase at the time of biodegradation of hydrocarbon. The biosurfactant producing conditions were optimized as pH 7.0, temperature 40°C, 2% sucrose and 3% of yeast extract as best carbon and nitrogen sources for maximum production of biosurfactant (4.85 g l-1). Specifically, the low molecular weight compounds, i.e., C10-C14 were completely degraded, while C15-C19 were degraded up to 97% from the total hydrocarbon pools. Overall crude oil degradation efficiency of the strain A1 was about 87% within a short period of time (7 days). The accumulated biosurfactant from the biodegradation medium was characterised to be lipopeptide in nature. The strain A1 was found to be more robust than other reported biosurfactant producing bacteria in degradation efficiency of crude oil due to their enzyme production capability and therefore can be used to remove the hydrocarbon pollutants from contaminated environment.